Effect of nocturnal hypoxemia on glycemic control among diabetic Saudi patients presenting with obstructive sleep apnea - Mahmoud, Mahmoud I.; Alotaibi, Raed K.; Almusally, Rayyan; Shafiek, Hanaa; Elamin, Yasir; Alhaj, Ziad; AlBaker, Waleed; Elfaki, Alaeldin; Qutub, Hatem; Albahrani, Suha J.; Alabdrabalnabi, Fatima M.; Al Saeed, Zahra A.; et al. (Frontiers in Endocrinology, 2023)
Background: Obstructive sleep apnea (OSA) is a prevalent disease that is associated with an increased incidence of type II diabetes mellitus (DM) if left untreated. We aimed to determine the association between glycosylated hemoglobin (HbA1c) levels and both nocturnal hypoxemia and apnea-hypopnea index (AHI) among a Saudi patients with OSA. Methods: A cross-sectional study that enrolled 104 adult patients diagnosed with DM and confirmed to have OSA by full night attended polysomnography between 2018 and 2021. Those who presented with acute illness, chronic obstructive pulmonary disease (COPD)/restrictive lung diseases causing sleep-related hypoxemia, or no available HbA1c level within 6 months before polysomnography were excluded from the study. Univariate and multivariate linear regression analyses between HbA1c levels and parameters of interest were tested. Results: Sixty-eight patients (65.4%) of the studied population had uncontrolled DM (HbA1c ≥7%). In univariate regression analysis, there was a significant positive association between HbA1c, and sleep time spent with an oxygen saturation below 90% (T90), female gender, and body mass index (BMI) (p<0.05) but not AHI, or associated comorbidities (p>0.05). In the multivariate analysis, HbA1c was positively associated with increasing T90 (p<0.05), and ODI (p<0.05), but not with AHI (p>0.05). Conclusion: Nocturnal hypoxemia could be an important factor affecting glycemic control in patients with OSA suffering from DM irrespective of the severity of both diseases. Keywords: glycosylated hemoglobin, apnea/hypopnea index, hypoxia, hypoxemia, obstructive sleep apnea